Highly Selective Recovery of Lanthanides by Using a Layered Vanadate with Acid and Radiation Resistance. (17th December 2019) - Sun, Haiyan; Liu, Yang; Lin, Jian; Yue, Zenghui; Li, Weian; Jin, Jiance; Sun, Qian; Ai, Yuejie; Feng, Meiling; Huang, Xiaoying
Abstract: It is of vital importance to capture lanthanides (nuclear fission products) from waste solutions for radionuclide remediation owing to their hazards. The effective separation of lanthanides are achieved by an acid/base‐stable and radiation‐resistant vanadate, namely, [Me2 NH2 ]V3 O7 (1 ). It exhibits high adsorption capacities for lanthanides ( qm Eu =161.4 mg g −1 ; qm Sm =139.2 mg g −1 ). And high adsorption capacities are maintained over a pH range of 2.0–6.9 ( qm Eu =75.1 mg g −1 at low pH of 2.5). It displays high selectivity for Eu 3+ (simulant of An 3+ ) against a large excess of interfering ions. It can efficiently separate Eu 3+ and Cs + (or Sr 2+ ) with the highest separation factor SFEu/Cs of 156 (SFEu/Sr of 134) to date. The adsorption mechanism is revealed by calculations and XPS, EXAFS, Raman, and elemental analyses. These merits combined with facile synthesis and convenient elution makes the title vanadate a promising lanthanide scavenger for environmental remediation. Abstract : Eine selektive Rückgewinnung von Lanthanoiden gelingt mithilfe eines einfachen kristallinen Vanadats mit Säure‐ und Strahlungsbeständigkeit. Das Vanadat zeichnet sich durch hohe Kapazitäten, exzellente Selektivität für Lanthanoide und leichte Elution aus. Der Adsorptionsmechanismus wurde durch Rechnungen sowie XPS, EXAFS, Raman‐Spektroskopie und Elementaranalyse aufgeklärt. Diese Arbeit unterstützt die Entwicklung kristalliner Vanadate für die Umweltsanierung.